2021
DOI: 10.17582/journal.sja/2021/37.2.573.585
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Moringa Leaves Powder as a Supplement in Whole Wheat Flour Biscuit

Abstract: Wheat flour biscuits are of widely consumed bakery products and mostly considered as nutritionally poor due to lacking in certain essential micronutrients. Moringa leaves are very rich in nutrients namely proteins, fibers and minerals. Keeping in view the nutritional importance of moringa leaves powder, the present study was carried out to investigate the effect of moringa leaves enrichment on the overall quality of whole wheat flour biscuits. Composite flours were made by incorporating moringa leaves powder i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
1
3
1
Order By: Relevance
“…This may be due to the significant decrease in thickness of the cookies. The spread ratio (7.91–10.05) of the enriched cookies in this study was higher than values previously reported (4.05–7.04) for wheat flour enriched with ND-MOLP [ 17 , 48 ]. A high spread ratio value is desirable and is usually associated with better cookie quality [ 49 , 50 ].…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…This may be due to the significant decrease in thickness of the cookies. The spread ratio (7.91–10.05) of the enriched cookies in this study was higher than values previously reported (4.05–7.04) for wheat flour enriched with ND-MOLP [ 17 , 48 ]. A high spread ratio value is desirable and is usually associated with better cookie quality [ 49 , 50 ].…”
Section: Resultscontrasting
confidence: 90%
“…Watters [ 51 ] reported a decrease in spread ratio value for cookies supplemented with non-wheat flours and associated the decrease to competition by the non-wheat flours for limited free water available in the cookie dough. The competition for water is thought to result in the formation of aggregates which increases the number of hydrophilic sites in the flour [ 48 ]. During dough formation, free water is partitioned between the hydrophilic sites, thereby increasing dough viscosity [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample D had the highest moisture content while sample B had the lowest moisture content. The moisture content of the bread samples recorded in this work was found to be significantly higher than that reported by Dabels et al (2016) and Riaz et al (2007) but within the values reported by (Coppock et al, 2009). High moisture content above 10% may not be favorable for the storage of products (Christiana & Nkemakonam, 2018).…”
Section: Resultssupporting
confidence: 87%
“…The method of Riaz et al(2007) was used to prepare mung bean flour. Mung beans were cleaned manually by hand‐picking the chaff and other extraneous material.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research show that cookies prepared using moringa leaves powder resulted in increase of proteins, fibers and mineral content (Ca, Fe, P, K) of the cookies significantly (Dachana et al, 2010;Abdel-Samie and Abdulla, 2014;Mouminah, 2015). Adding moringa leaves powder to biscuit also affected the physical attributes and acceptability of the biscuit (Riaz and Wahab, 2021;Dachana et al, 2010). These authors and Hedhili et al (2021) suggested that the limit of moringa supplemnation in cookies is upto 10%.…”
Section: Introductionmentioning
confidence: 96%